2006
DOI: 10.1097/01.hjh.0000239299.71001.77
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced sodium sensitivity and disturbed circadian rhythm of blood pressure in essential hypertension

Abstract: In patients with essential hypertension, an inter-relationship exists among metabolic syndrome, enhanced sodium sensitivity of the blood pressure and non-dipping. The elevated risk of cardiovascular diseases in patients with metabolic syndrome may be related to sodium-sensitive hypertension and non-dipping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
91
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 30 publications
(38 reference statements)
4
91
2
1
Order By: Relevance
“…[1][2][3][4][5] Although the pathogenesis of salt sensitivity is unknown, both genetic and environmental factors appear to interact to determine the exaggerated BP response to changes in salt intake. [6][7][8][9][10][11][12][13][14][15] Increased reactivity of BP to salt is commonly observed in subjects with obesity and associated cardiovascular risk factors. [6][7][8][9][10] Insulin resistance, hypertension, increased sympathetic activity, endothelial dysfunction and abnormal nitric oxide (NO) bioactivity are among the list of factors that have been proposed to directly or indirectly lead to salt sensitivity related to obesity.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Although the pathogenesis of salt sensitivity is unknown, both genetic and environmental factors appear to interact to determine the exaggerated BP response to changes in salt intake. [6][7][8][9][10][11][12][13][14][15] Increased reactivity of BP to salt is commonly observed in subjects with obesity and associated cardiovascular risk factors. [6][7][8][9][10] Insulin resistance, hypertension, increased sympathetic activity, endothelial dysfunction and abnormal nitric oxide (NO) bioactivity are among the list of factors that have been proposed to directly or indirectly lead to salt sensitivity related to obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier data have also provided evidence that there might be an inter-relationship between MetS, enhanced sodium sensitivity of the blood pressure and non-dipping pattern. 9 Little is known about the relationship between the circadian profile of blood pressure, dipping pattern and insulin, as well as glucose metabolism in subjects without any known metabolic diseases. Therefore, we investigated the possible association between 24-h blood pressure profile and glucose tolerance status, MetS, as well as its components in a large population-based cohort (n¼462) without diagnosed hypertension or diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…However, several other neurohormonal systems regulating BP have been shown to follow a circadian rhythm and may contribute to the circadian variations in BP. 11,12 Some studies have suggested that the reduction or even the inversion of the usual nocturnal dipping in some subjects is associated with high sodium intake and salt sensitivity [13][14][15][16][17] . Recently, Fukuda et al 18 proposed a hypothesis according to which the nondipping pattern of BP at night is because of an impaired capacity to excrete sodium during daytime.…”
mentioning
confidence: 99%